ANALISIS PELAKSANAAN PROGRAM KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus Pada Perkebunan Kelapa Sawit PT. Prima Agro Aceh Lestari Kabupaten Aceh Barat) - Ahmad Arkadius (Jurnal Bisnis Tani, 2018)
As a source of vegetable oil, palm oil can be a poverty alleviation tool, food, and energy sources. The development of palm oil plantations requires much labor, and this means that palm oil plantations are labor-intensive businesses so that the management of occupational health and safety is essential. The purpose of this study was to determine the effect of occupational safety and health on the PT. Prima Agro Aceh Lestari (PAAL) employees' performance in West Aceh Regency. The results of this study showed that workers' protection, worker health maintenance, and workplace safety had a positive effect and had a strong relationship to employee's performance. Simultaneously, worker protection, maintenance of workers' health and safety in the workplace correlate to employee performance, but partially, only worker protection and worker health maintenance that affect employee's performance. In addition to the research variables, there are still other factors that are also strong in influencing the performance of employees of PT. Prima Agro Aceh Lestari (PAAL).